Social Loafing: A Model to Determine Factors Affecting Generating Knowledge Teams of Social Science (With Emphasis on Theses) - Moslem Bagheri; Qasem Salimi; Banafsheh Akbari (بهبود مدیریت, 2014)
In the Information age, those societies will move in the path of growth and continuous development that their cycle of knowledge and innovation have boom and greater durability. In the meantime, universities and centers of higher education, as main site of generating knowledge, play an important role in growth and development of a country; though, it’s essential to study and pathology the system of generating knowledge in university and the quality of its researches continuously to be protected from probable harm. Theses are one of the most important sources of generating science in universities, if the process of compilation and evaluation goes right, we can be hopeful about universities generating science. However, this process take place in a team includes: student, supervisor professor, advisor professor, and referee professor, in some cases we see social loafing phenomena occurring in this group, so researchers put their purpose on identifying critical factors affecting social loafing and apply Exploratory mixed methods study and Qualitative content analysis in qualitative section, use survey method and structural equation modeling in quantitative section to identify effective factors on social loafing. After achieving theoretical adequacy in interviewing experts and accomplishing Qualitative content analysis for interviews, proceed to distribute the questionnaire with survey method and grouping 14 effective factors on social loafing in compiling theses of Social Science in tow category : team based (including members of the profound lack of interest, time limit of Members, inappropriate subject matter related to the lack of expertise of teachers, lack of communication within the team, conservative members, number of members, their perceptions errors) and meta-team-based factors (such as lack of teamwork in the country, the University’s policies, procedures thesis distribution, optimal lack of supervision, lack of resources provided by the university research, materialistic approach to science and unscientific behavior) have achieved.